Bacterial Infections and Inflammatory Markers in Diabetic Foot Ulcers: Assessing the Roles of Staphylococcus aureus, Pseudomonas aeruginosa, Vascular Endothelial Growth Factor, and Interleukin-6 - Sarah Kadhim Abbas; Dakhel Ghani Omran; Lubna Abdulazeem (Medical Journal of Babylon)
Background:Diabetic foot ulcers (DFUs) are severe complications of diabetes, leading to osteomyelitis, gangrene, and limb amputation. These outcomes increase mortality risk and bacterial resistance in surviving patients. The selection of the most effective antibiotics for DFUs remains a growing challenge. Objectives:The study aimed to identify risk factors, bacterial pathogens, and drug resistance in DFU patients, and explore the correlation between interleukin-6 (IL-6), vascular endothelial growth factor (VEGF) levels, and DFUs. Materials and Methods:Sixty isolates of bacteria were isolated aerobically from 100 samples of DFU (30 isolates from Pseudomonas aeruginosa and 30 isolates from Staphylococcus aureus). All isolates were identified by biochemical tests, then confirmation diagnosis was done by using VITEK-2. Determination multiple drug resistance isolates by susceptibility tests, then estimation of the activity of silver nanoparticles (AgNPs) as antibacterial with different concentrations were done. VEGF and IL-6 levels were determined by using Enzyme-linked immunosorbent assay (ELISA) technique. Results:The study revealed that many bacteria-resistant antibiotics, but AgNPs significantly inhibit multi-drug resistant bacteria, suggesting their potential as an alternative treatment. VEGF and IL-6 levels were significantly higher (P-value < 0.001) in DFU patients, with IL-6 negatively correlating with VEGF. Conclusion:Diabetic foot infections, caused by various bacteria, require understanding of antibiotic sensitivity for effective treatment. AgNPs showed strong antimicrobial effects against common bacteria, suggesting potential as an alternative treatment. The study also found elevated VEGF and IL-6 levels in DFU patients, with IL-6 potentially inhibiting VEGF, thus impairing healing.